Beneficial effects of tuna hydrolysate in poultry by-product meal diets on growth, immune response, intestinal health and disease resistance to Vibrio harveyi in juvenile barramundi, Lates calcarifer. Issue 89 (June 2019) - Siddik, Muhammad A.B.; Howieson, Janet; Fotedar, Ravi
Abstract: This study was conducted to investigate the effects that tuna hydrolysate (TH) supplementation in poultry by-product meal (PBM) diets would have on growth, immunity and resistance to Vibrio harveyi infection in juvenile barramundi, Lates calcarifer . Five isonitrogenous and isocaloric diets containing fishmeal (FM) without TH supplementation (control) and four diets with 10% TH supplementation viz. a FM protein diet (FMBD + TH), a 75% PBM protein diet (LPBM + TH) and two 90% PBM protein diets, either bioprocessed (BPBM + TH) or unprocessed (HPBM + TH), were formulated for juvenile barramundi, Lates calcarifer . The diets were fed to triplicate groups of juvenile barramundi (average pool weight 12.63 ± 0.11 g) for 10 weeks. Significantly (P < 0.05) higher final body weights and specific growth rates were noted in fish fed with FMBD + TH and BPBM + TH diets when compared to the control. Transmission electron microscopy observation of fish distal intestines revealed a significant enhancement of microvilli length in fish fed FMBD + TH and BPBM + TH whereas scanning electron microscopy analysis found no significant difference in microvilli density. A bacterial challenge with Vibrio harveyi was conducted for 14 days after the growth trial to test the immune response and survival of barramundi. In the pre-challenge condition, a significant reduction in blood glucose was found in BPBM + TH compared to the control, and fish in the post-challenge at 24 h had higher glucose levels compared to fish in the pre- and post-challenge conditions at 72 h. The serum lysozyme activity was significantly higher in FMBD + TH and BPBM + TH compared to the control and fish at 72 h post-challenge exhibited higher lysozyme activity in each treatment compared to all dietary groups in the post-challenge condition at 24 h and to HPBM + TH and BPBM + TH in the pre-challenge condition. Fish fed FMBD + TH, LPBM + TH and BPBM + TH diets had significantly higher survival to the bacterial challenge than fish in the control and HPBM + TH. These results showed that PBM supplemented with TH could successfully replace FM without compromising growth, however, bioprocessed PBM supplemented with TH (BPBM + TH) may significantly improve growth performance, immune response, intestinal health and disease resistance in juvenile barramundi. Highlights: Poultry by-products meal bioprocessed by Saccharomyces cerevisiae and Lactobacillus casei and supplemented with 10% tuna hydrolysate promotes growth performance and intestinal mucosal morphology of barramundi. Ten percent tuna hydrolysate supplementation in bioprocessed poultry by product meal based diet enhances the innate immunity of the barramundi against Vibrio harveyi infection. Supplementation of tuna hydrolysate is recommended for non-fishmeal based barramundi diets.